Testing Indonesia’s decisiveness: Vietnam’s continuous presence in the North Natuna Seas - Putra, Bama Andika (Frontiers in Political Science, 2024)
In December 2022, Indonesia and Vietnam concluded the EEZ boundary lines that have been under negotiations for 12 years. Through this, it is expected that intrusions made by Vietnamese maritime constabulary forces into Indonesia's North Natuna Seas can end. On the contrary, intrusions have risen in the first eight months of 2023, indicating Vietnam's intent to continue its maritime-based operations in the grey-zone areas of Indonesian waters. In making sense of this developing crisis, this article adopts secondary data from the Indonesia Open Justice Initiative between January 2023 and August 2023. In tracking the instances of intrusions, it utilizes an Automatic Identification System obtained from Marine Traffic. The analysis is made by framing the crisis under the maritime diplomatic framework, which concludes that Vietnam is persistent with its maritime diplomatic strategy of 'paragunboat diplomacy' in showcasing effective occupancy in grey zone areas.